2021
DOI: 10.5397/cise.2021.00290
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of extensor muscle strengthening exercise by itself, exercise with polydeoxyribonucleotide injection, and exercise with extracorporeal shockwave therapy in lateral epicondylitis: a randomized controlled trial

Abstract: Background: Extensor muscle strengthening exercises with counterforce bands (EX) is a conventional conservative treatment for lateral epicondylitis (LE) of the elbow. In addition, polydeoxyribonucleotide (PDRN) or extracorporeal shockwave therapy (ESWT) has been recently used for tennis elbow.Methods: Sixty-three patients with chronic LE participated in this study and randomly allocated in three groups (G1: EX, G2: EX+PDRN injection, and G3: EX+ESWT). All of the three groups were taught to perform EX at the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…After combining selected studies to estimate the precise effect of ESWT on the crude average pain score in patients with LE, the results showed that, overall, the average pain in these patients decreased by 0.63 units based on the crude score of the VAS tool. While the diagnosis of LE is usually straightforward, its treatment presents several challenges [ 49 , 129 , 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…After combining selected studies to estimate the precise effect of ESWT on the crude average pain score in patients with LE, the results showed that, overall, the average pain in these patients decreased by 0.63 units based on the crude score of the VAS tool. While the diagnosis of LE is usually straightforward, its treatment presents several challenges [ 49 , 129 , 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRP injections have been used, yielding mixed results-promising according to some studies, but less so in others [25][26][27]. Additionally, polydeoxyribonucleotide injections are a consideration, particularly since a combination of polydeoxyribonucleotide injections and exercises to strengthen the extensor muscles showed superior improvement in functional scores when compared to exercises alone or exercises combined with extracorporeal shock wave therapy (ESWT) [31].…”
Section: Lateral Elbow Painmentioning
confidence: 99%
“…If epicondylitis remains unimproved after 3 to 6 months of treatment, it is considered refractory and surgical intervention may be indicated. Conservative treatment encompasses exercise therapy, physical therapy, drug therapy, bracing, extracorporeal shock wave therapy, percutaneous pie crusting of the tendon origin [9] polydeoxyribonucleotide injections [10], platelet-rich plasma (PRP) injections [11], autologous blood injections [12], and local corticosteroid injection therapy.…”
Section: )Medialepicondylitismentioning
confidence: 99%